Lexically driven selective adaptation by ambiguous auditory stimuli occurs after limited exposure to adaptors - Llompart Garcia, Miguel; Casillas, Joseph V. (Journal of the Acoustical Society of America, 2016)
Limited exposure to ambiguous auditory stimuli results in perceptual recalibration. When unambiguous stimuli are used instead, selective adaptation (SA) effects have been reported, even after few adaptor presentations. Crucially, selective adaptation by an ambiguous sound in biasing lexical contexts had previously been found only after massive adaptor repetition [Samuel (2001). Psychol. Sci. 12(4), 348-351]. The present study shows that extensive exposure is not necessary for lexically driven selective adaptation to occur. Lexically driven selective adaptation can arise after as few as nine adaptor presentations. Additionally, build-up course inspection reveals several parallelisms with the time course observed for SA with unambiguous stimuli. (c) 2016 Acoustical Society of America